Microsoft Access 2002 fast & easy - Wempen, Faithe (Prima Pub. RosevilleUS, 2001)
Provides beginning to intermediate computer users with step-by-step visual instructions for performing essential tasks. Presents topics sequentially, beginning with creating a new database, and including: working with tables; entering, editing, viewing and finding data; creating and using forms; and working with the web. Includes 4 appendices of specialized information, for example, installing Access 2002 and Office XP; and provides a glossary of important Access terminology.